2014
DOI: 10.1021/jz5022685
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Electron Transfer in Engineered Azurins Exhibits Marcus Inverted Region Behavior

Abstract: The Marcus theory of electron transfer (ET) predicts that while the ET rate constants increase with rising driving force until it equals a reaction's reorganization energy, at higher driving force the ET rate decreases, having reached the Marcus inverted region. While experimental evidence of the inverted region has been reported for organic and inorganic ET reactions as well as for proteins conjugated with ancillary redox moieties, evidence of the inverted region in a "protein-only" system has remained elusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
(71 reference statements)
2
29
0
Order By: Relevance
“…This lowering of reorganization energy is attributed to an increase in flexibility of the copper site for these mutants [291]. By considering more variants in SCS using the guidelines provided by previous studies, [235] they showed experimental evidence of the Marcus inverted region in a non-derivatized protein system [292] (Figure 28). …”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowering of reorganization energy is attributed to an increase in flexibility of the copper site for these mutants [291]. By considering more variants in SCS using the guidelines provided by previous studies, [235] they showed experimental evidence of the Marcus inverted region in a non-derivatized protein system [292] (Figure 28). …”
Section: Case Studiesmentioning
confidence: 99%
“…Plot of ET rate vs. driving force of intermolecular ET in several azurin mutants, Reprinted with permission from [292]. Copyright {2015} American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…Scott et al [43] studied intramolecular ET in cytochrome b 5 labeled with Ruthenium(II) polypyridine complexes with different E m values. Farver et al [44] recently studied the intramolecular ET reactions between the copper of azurin a disulfide radical anion with several site-directed mutants that spanned a wide range of E m values. The ΔG°-dependence of the ET reaction between MADH and amicyanin had previously been examined by looking at the rates of the forward and reverse reactions of amicyanin with different redox forms of MADH [19, 21].…”
Section: Discussionmentioning
confidence: 99%
“…λ values have also been determined for ET reactions between native redox cofactors and redox-active active tags such as Ruthenium complexes [30, 31]. ET reactions between the copper of azurin a disulfide radical anion were used to determine λ [32]. The proteins used in the present study are among the few for which λ values have been experimentally determined for the reactions with their natural redox partners; the reactions of amicyanin with MADH [33] and cytochrome c -551i [34], and the reactions between MauG and preMADH and MADH [11].…”
Section: Discussionmentioning
confidence: 99%